Medical students’ knowledge and competence in fundamental communication skills - Gurjeet Singh; Raksha Singh; K. R. Sethuraman (MGM Journal of Medical Sciences)
Effective communication is a fundamental component of high-quality medical care, enabling healthcare providers to establish therapeutic relationships that foster patient-centered outcomes. In clinical settings, clear communication between the provider and patient plays a vital role in shared decision-making and the development of self-management strategies, particularly for elderly patients. This rapid review aims to synthesize the impact of communication quality and effectiveness on patient-centered outcomes in geriatric care. Despite its importance, communication skills are often not formally taught in many medical schools, presenting significant challenges in clinical practice. The National Medical Commission emphasizes the importance of essential communication skills, including active listening, empathy, delivering clear explanations, asking open-ended questions, and acknowledging cultural diversity. Practicing these skills across various clinical scenarios can lead to more accurate diagnoses, improved treatment outcomes, quicker recovery, and greater patient satisfaction. To ensure effective communication, reliable performance assessment tools, such as the objective structured clinical examination, are crucial. These tools help identify gaps in communication skills and provide guidance for targeted improvements.